ANALISA HUKUM WARIS ADAT BALI TERHADAP PEWARISAN WANITA HINDU BALI - Matthew Jeremia; Michael Michael; Martin Izha Mahendra; Jeane N. Selly (Realism: Law Review, 2023)
This research aims to analyze the Balinese Customary Inheritance Law in the context of inheritance for Hindu women in Bali. The Balinese customary inheritance law has a strong tradition and significant influence on the distribution of inherited wealth among the Hindu community in Bali. This research explains the principle of "pandeka sawah" as the foundation of the Balinese customary inheritance system, where the eldest son has greater rights to inheritance compared to daughters. However, this research also highlights the social and cultural developments that have influenced changes in gender equality values and the protection of women's rights. In this context, the research analyzes how traditional inheritance practices have undergone revisions and adjustments to respect women's rights. The research also describes how Balinese families or communities adopt fair inheritance rules for women, including providing equal rights in inheritance. The study involves an analysis of the development of national laws in Indonesia, particularly the Marriage Law, which protects women's rights in inheritance. Through this research, it is expected to provide a better understanding of the Balinese customary inheritance law regarding the inheritance of Hindu women in Bali and its implications for gender equality in cultural and legal contexts.